Characteristics of urban milkweed gardens that influence monarch butterfly egg abundance - Klinger, Karen R.; Hasle, Aster F.; Oberhauser, Karen S. (Frontiers in Ecology and Evolution, 2024)
The eastern population of monarch butterflies (Danaus plexippus) has dramatically declined in the last few decades, which is largely attributed to a loss of milkweed habitat in agricultural areas. Residential land in metropolitan areas has the potential to provide a significant source of the milkweed needed to support the monarch population. To examine if and how urban milkweed patches can support monarch butterflies, we worked with community scientists in the Chicago metropolitan area to monitor monarch eggs and caterpillars in yards and community gardens. We hypothesized that the largest numbers of eggs (i.e. gardens that were most attractive to monarchs) would be observed in patches that were older, had a high abundance of milkweed, contained more than one species of milkweed including Asclepias syriaca (common milkweed) and/or A. incarnata (swamp milkweed), and had a large diversity of nectar plants. All patches were assessed at their peak egg count each year, which ranged from zero to 170 eggs in a given observation. To determine which characteristics were most influential to egg presence, we examined patches where eggs were present or absent during this peak observation. For abundance, we divided these peak observations into whether or not the egg counts were in the top 20% in a given year, excluding patches where eggs were absent, and assessed their patch characteristics. Our results show that patch age and presence of A. syriaca affected whether patches contained eggs or not. We also found that patches with the largest number of eggs observed tended to have A. syriaca, more milkweed plants, and a higher diversity of blooming plant species. The data we collected from community scientists in the Chicago area has enhanced our understanding of how urban gardeners can create effective breeding habitats for monarch butterflies. By planting Asclepias syriaca within its natural range, along with other native milkweed species and a diverse selection of flowering plants, individuals can create gardens that serve as excellent habitats for monarchs and other pollinators.